2019
DOI: 10.1177/0300060519860686
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of the blood monocyte–lymphocyte ratio in knee osteoarthritis

Abstract: Objective Knee osteoarthritis (KOA) is a chronic inflammatory disease. The monocyte–lymphocyte ratio (MLR) was reported to be a non-invasive, cost-effective marker in various systemic diseases, but it has not yet been investigated in KOA. This cross-sectional study evaluated the diagnostic value of MLR in KOA. Methods Two hundred and five KOA patients and 120 healthy control subjects were enrolled. Patient data, including age, sex, blood cell counts, erythrocyte sedimentation rate (ESR), C-reactive protein (CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 29 publications
3
33
0
2
Order By: Relevance
“…11 El último índice utilizado es el monocito/linfocito (IML), cuya mayor utilidad se ha observado en enfermedades inflamatorias como predictor de un ataque agudo de gota u osteoartritis, en las cuales el incremento del índice se asoció a exacerbaciones articulares. 12,13 La infección por COVID-19 se caracteriza por inflamación sistémica no regulada denominada "tormenta de citocinas", cuyo desarrollo se basa en la activación descontrolada de la respuesta inmune innata, lo que pone en marcha el endotelio, el complemento y el sistema de hemostasia. 14,15 Esta activación modifica los diferentes conteos celulares y ocasiona linfopenia profunda, leucocitosis y neutrofilia.…”
Section: Introductionunclassified
“…11 El último índice utilizado es el monocito/linfocito (IML), cuya mayor utilidad se ha observado en enfermedades inflamatorias como predictor de un ataque agudo de gota u osteoartritis, en las cuales el incremento del índice se asoció a exacerbaciones articulares. 12,13 La infección por COVID-19 se caracteriza por inflamación sistémica no regulada denominada "tormenta de citocinas", cuyo desarrollo se basa en la activación descontrolada de la respuesta inmune innata, lo que pone en marcha el endotelio, el complemento y el sistema de hemostasia. 14,15 Esta activación modifica los diferentes conteos celulares y ocasiona linfopenia profunda, leucocitosis y neutrofilia.…”
Section: Introductionunclassified
“…These findings are similar to previous research that examined the dynamics of these factors in patients with arthritis, which was carried out by the authors of this article. 15 Based on ROC curve analyses, AFR and MLR had higher diagnostic values than NLR and PLR. In addition, correlation analyses indicated that AFR was negatively correlated with monocytes and MLR.…”
Section: Discussionmentioning
confidence: 97%
“…These findings are similar to previous research that examined the dynamics of these factors in patients with arthritis, which was carried out by the authors of this article. 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Counts of white blood cells (WBC), red blood cells (RBC), neutrophils, monocytes, lymphocytes and platelets were performed in samples of peripheral blood obtained by standard venipuncture in K 2 EDTA BD vacutainers using an automatic flow cytometry analyzer (CELL-DYN Ruby System; Abbott Diagnostics). Using the hematological data, we calculated the monocyte/lymphocyte ratio (MLR), neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR) by dividing the number of respective subtypes of blood cells (monocytes, neutrophils and platelets) by lymphocyte number (21) and also a systemic immune-inflammation index (SII) according to the formula: SII=platelet count x neutrophil count/lymphocyte count (22). The erythrocyte sedimentation ratio (ESR) was assessed according to the Westergren method.…”
Section: Statement Of Ethics According To the European Unionmentioning
confidence: 99%